2021
DOI: 10.1055/a-1470-6050
|View full text |Cite
|
Sign up to set email alerts
|

Highly Fluorinated Trianglimine Macrocycles: A Supramolecular Organic Framework

Abstract: In a two-step synthesis, a novel highly fluorinated dialdehyde is accessible. This very reactive building block for dynamic imine chemistry is exemplarily utilized in a condensation reaction to generate the first extensively fluorinated trianglimine. The analysis of the material properties and especially the crystal structure of the [3+3] macrocycle reveal a supramolecular organic framework with tubular porous channels. The use of fluorinated ligands to generate hydrophobic, electron-deficient channel-like por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
0
12
0
2
Order By: Relevance
“…A highly fluorinated trianglimine macrocycle T4 was synthesized and exhibits a chiral helical pore in the solid-state with again accessible voids depicted in dark blue, stable also upon desolvation. [27] Structures determined from SXRD with hydrogen atoms and solvent molecules omitted for clarity. The quality of the collected data was not sufficient to determine the nature of the iodo-species entrapped within the channels, however, Raman studies revealed the presence of polyiodide (I 3 À and I 5 À ) rather than iodine.…”
Section: Triangliminesmentioning
confidence: 99%
See 4 more Smart Citations
“…A highly fluorinated trianglimine macrocycle T4 was synthesized and exhibits a chiral helical pore in the solid-state with again accessible voids depicted in dark blue, stable also upon desolvation. [27] Structures determined from SXRD with hydrogen atoms and solvent molecules omitted for clarity. The quality of the collected data was not sufficient to determine the nature of the iodo-species entrapped within the channels, however, Raman studies revealed the presence of polyiodide (I 3 À and I 5 À ) rather than iodine.…”
Section: Triangliminesmentioning
confidence: 99%
“… [22b] Following these initial results, a variety of articles were published in close succession, mainly focusing on the synthetical aspects, [22‐23] such as diversification by formaldehyde tying, [22a] the inherent chirality or host‐guest interactions in solution, [23] obtained crystal structures mainly being a supplement. Although even in the earliest works either inclusion complexes or pores, when omitting the solvent from the structure, could be observed in the solid‐state, [22c,24] it took another decade until groups started focusing on the solid‐state adsorption properties [24–27] . Other than POCs with their inherent 3‐dimensional cavity, in the 2‐dimensional structure of macrocycles only a planar void (hole) is present.…”
Section: Triangliminesmentioning
confidence: 99%
See 3 more Smart Citations